2018
DOI: 10.3748/wjg.v24.i25.2764
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis on the association of tuberculosis in Crohn’s disease patients treated with tumor necrosis factor-α inhibitors (Anti-TNFα)

Abstract: AIMTo perform a meta-analysis on the risk of developing Mycobacterium tuberculosis (TB) infection in Crohn’s disease (CD) patients treated with tumor necrosis factor-alpha (TNFα) inhibitors.METHODSA meta-analysis of randomized, double-blind, placebo-controlled trials of TNFα inhibitors for treatment of CD in adults was conducted. Arcsine transformation of TB incidence was performed to estimate risk difference. A novel epidemiologically-based correction (EBC) enabling inclusions of studies reporting no TB infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
1
17
1
1
Order By: Relevance
“…Interestingly, treatment of MAP-infected macrophages with anti-TNFα biologics increased MAP survival and burden, and led to excessive inflammatory response [25]. This is consistent with other studies, which reported a rise in M. tuberculosis infection in patients on anti-TNFα treatment [30]. In this study, we confirmed the presence of MAP infection in the blood of RA patients; the majority of these patients were on anti-TNFα treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, treatment of MAP-infected macrophages with anti-TNFα biologics increased MAP survival and burden, and led to excessive inflammatory response [25]. This is consistent with other studies, which reported a rise in M. tuberculosis infection in patients on anti-TNFα treatment [30]. In this study, we confirmed the presence of MAP infection in the blood of RA patients; the majority of these patients were on anti-TNFα treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Genetic polymorphisms in TNFRSF1A and TNFRSF1B were found to be correlated with anti-TNFα treatment response in patients with CD. Specifically, the TNFRSF1A:rs767455 AG and GG genotype has a significant difference in frequency among non-responders to anti-TNFα treatment compared with the majority of drug responders who had the AA genotype 16. Similarly, the TNFRSF1B:rs3397 CT and TT also have a significant difference in frequency among anti-TNFα non-responders in comparison to patients with CD who were classified as drug responders (CC genotype) 18 30.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, patients receiving anti-TNFα treatment are at higher risk for meningitis, sepsis, histoplasmosis, and pneumonia 10–12. Moreover, the risk for tuberculosis development has substantially increased in patients receiving anti-TNFα, which might raise a question about their effect on Mycobacterium avium subsp paratuberculosis (MAP) infection in a subset of patients with CD 13–16. Thus, prescribing anti-TNFα to patients with CD without considering MAP infection could worsen disease condition eventually.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the limitations of panel design, other NTM species, such as M. avium subsp. paratuberculosis (MAP), involved in the pathogenesis of Crohn's disease and other human autoimmune disorders, were uncovered in our study (Cao et al, 2018 ). To find out the cause of clinical infection symptoms, nested PCR or ELISA would be performed to identify these NTM species in our future study.…”
Section: Discussionmentioning
confidence: 83%